(untitled) (Orfeu, 2021)
This article presents an action research in four music classes in the first year of elementary school at a school in Rio de Janeiro. It aims to investigate theoretical and practical conditions for the use of soundtracks and for activities that derive from its interpretation as a complemen- tary teaching path. Multimedia langua- ge, combining audiovisual media with static elements such as images, texts and musical scores, was used as the main pedagogical tool. From this multimedia language, students composed music with narratives, sounds and images de- monstrating their understanding about the relationships between expression, communication, arts, and different cul- tures. As a result, there was the develop- ment of the flute instrument technique, reading skills in non-traditional and tra- ditional musical writing, and artistic ex- pressiveness.